Історичні постаті у царині метрології Галичини – професор доктор Й. К. Лісґаніґ (1719–1799) - Гапоненко, М. В.; Луцик, Я. Т.; Haponenko, M.; Lutsyk, Ya. (Видавництво Львівської політехніки, 2018)
Описано життєвий шлях та професійну діяльність видатного вченого – професора, д-ра Йозефа Ксавера Лісґаніґа (1719–1799). Особливу увагу звернуто на виконані ним перші градусні вимірювання в Австрійській імперії, кадастрове картографування Галичини, Володимирії та Буковини та створення першої державної метрологічної служби в Галичині, а саме у Львові.

In 2019, 100 years since the founding of the Department of Information and Measurement Technologies of the Lviv Polytechnic National University, there is an urgent need to look back in the historical perspective and analyze the contribution of certain historical figures to the development of engineering thought and the principles of metrology in the areas of Western Ukraine and, in particular, in the territories of Galychyna. First of all it concerns those individuals whose activities in Ukraine are insufficiently covered, and their merits can be considered undervalued precisely in the field of metrology and metrological support. In this regard, the figure of Joseph Xaver Liesganig, who is well-known in Europe as a prominent astronomer, geodesist, cartographer, mathematician, teacher, theologian, architect, builder, metrologist, designer of astronomical instruments and one of the pioneers in determining the size of the Earth. In Ukraine, are known not much information about the activities of Joseph Xaver Liesganig. In detail, the work of Joseph Xaver Liesganig was studied and analyzed by a graduate of the Lviv Polytechnic, and then an employee of the Research Geodetic, Topographic and Cartographic Institute in the Czech Republic Alexander Drbal. The article describes the life course and professional activities of the eminent scientist Professor Dr. Joseph Xaver Liesganig (1719–1799). Particular attention is paid to the first degree measurements made by him in the Austrian Empire, the cadastral mapping of Galychyna, Volodymyria and Bukovina and the creation of the first state metrology service in Galychyna, namely in Lviv. As you know, reference models with the state brand were stored in 18 cities of Galychyna: 198 measures of capacity, 36 measures of length, 360 units of measure of weight. For the supervision of measures, the Decree of December 5, 1785, at the Galychynian governorate, there was created the Inspectorate of Measures and Weights, the first state metrology service of Galychyna, the first in Ukraine. The duties of the inspectorate consisted of typing, implementation, supervision of compliance with measures and weights, training of responsible persons in district towns, making and adjusting of measuring instruments. The first inspector, part-time director of navigation and engineering in Galychyna, was precisely Joseph Xaver Liesganig.
Historical personality in the field of Galychyna metrology – professor doctor J. X. Liesganig (1719–1799)
Keywords: Йозеф Ксавер Лісґаніґ; геодезія; картографія; градусні вимірювання; вимірювання; державна метрологічна служба; Joseph Xaver Liesganig; Geodesy; Cartography; Degree Measurements; Measurements; State Metrology Services